Comparison of apical transportation and centering ability of Mtwo and Reciproc R25 in severely curved canals using cone-beam computed tomography - Abbas Mesgarani; Mahmoud Reza Hamidi; Sina Haghanifar; Shabnam Naiemi; Ali Bijani (Wolters Kluwer Medknow Publications, 2018)
Background: Apical transportation (AT) of the root canal moves the physiologic canal terminus to a new location on the external root surface and results in the accumulation of debris and residual microorganisms due to inadequate cleaning and shaping of the canal end. This study aimed to assess the prevalence of AT following canal preparation with Mtwo and Reciproc R25 using cone-beam computed tomographic (CBCT). Materials and Methods: In this in vitro study, 40 mesiobuccal root canals of the maxillary molars with 19-22 mm length and (>40°) taper were prepared in two groups using Mtwo and Reciproc R25 rotary systems along with irrigation with 2.5% NaOCl. CBCT scans were obtained of the canals before and after preparation under similar conditions, and the values were measured using the device software. The amount of AT was measured according to Gambill et al. Data were analyzed using SPSS 17 and Chi-square and t-tests. P < 0.05 was considered significant. Results: Both systems caused some degrees of AT. No significant difference was found between the two systems in terms of the amount and direction of AT (P > 0.05); overall, the frequency of AT toward the mesial wall was greater than that toward the distal direction. However, this difference was not statistically significant. Conclusion: The mean amount of AT and the ability to keep the instruments in severely curved canals were not significantly different in canals prepared by Mtwo and Reciproc rotary systems. Thus, these systems can be used in the clinical setting with the lowest risk of AT.